New conjugated meso-tetrathienylporphyrin-cored derivatives as two-photon photosensitizers for singlet oxygen generation. (June 2018) - Zhang, Xu; Abid, Seifallah; Shi, Limiao; Sun, Zhipeng; Mongin, Olivier; Blanchard-Desce, Mireille; Paul, Frédéric; Paul-Roth, Christine O.
Abstract: A series of conjugated meso -porphyrin dendrimers containing conjugated fluorenyl dendrons, incorporating overall either four (3 ) or eight (4 ) fluorenyl units have been synthesized and characterized. These new molecular architectures are based on a central meso -tetra(thien-2-yl)porphyrin core (TThP ). Their linear optical properties, absorption and photoluminescence, as well as selected nonlinear optical properties, were investigated and compared to those of the unsubstituted meso -(thien-2-yl)porphyrin core (5 ) and also to those of previously reported analogues featuring 1, 4-phenylene groups (1 and2 ) in place of 2, 5-thienylene moieties. The positive role of these thienylene linkers over phenylene linkers on the two-photon absorption (2PA) cross-sections is clearly evidenced. Graphical abstract: A new family of conjugated meso -tetrathienylporphyrin-based dendrimers with fluorenyl arms has been synthesized. Their detailed luminescence properties and selected photophysical properties are discussed in the frame of two-photon-induced theranostics. Highlights: Two new meso-tetra(thien-2-yl)porphyrins3 and4 have been obtained and characterized. The two-photon absorption (2PA) cross-sections (σ2 ) of3 and4 were measured by TPEF, revealing strongly enhanced σ2 . Replacement of the 1, 4-phenylene spacer at the periphery of the porphyrin core by a 2, 5-thienylene one allows improvement of the 2PA cross-sections. Porphyrins3 and4 are efficient Two-photon Photosensitizers for Singlet Oxygen Generation.